Colonization of plastic debris by the long-lived precious red coral Corallium rubrum: New insights on the "plastic benefits" paradox. (April 2021) - Carugati, Laura; Bramanti, Lorenzo; Giordano, Bruna; Pittura, Lucia; Cannas, Rita; Follesa, Maria Cristina; Pusceddu, Antonio; Cau, Alessandro
Abstract: Seafloor macrolitter is ubiquitous in world's oceans; still, huge knowledge gaps exist on its interactions with benthic biota. We report here the colonization of plastic substrates by the Mediterranean red coral Corallium rubrum (L. 1758), occurring both in controlled conditions and in the wild at ca. 85 m depth in the Western Mediterranean Sea. Juveniles settled on seafloor macro-litter, with either arborescent or encrusting morphology, ranging from 0.6 to 3.5 mm in basal diameter and 0.2–7.1 years of age, also including a fraction (20%) of potentially sexually mature individuals. In controlled conditions, larvae settled and survived on plastic substrates for >60 days. Our insights show that marine plastic debris can provide favourable substrate for C. rubrum settlement either in controlled conditions or in the wild, suggesting their possible use in restoration activities. However, we pinpoint here that this potential benefit could result in adverse effects on population dynamics. Highlights: The colonization of plastic substrates by Corallium rubrum is documented. Branched end encrusting morphologies were observed. Colonies age was estimated to be up to ca. 7 years according to basal diameter. Ca. 20% of settled juveniles were potentially mature. Potential adverse effects on population dynamics are discussed.